(untitled) (Research, Society and Development, 2022)
The present study analyzed the use of early mobilization (PM) in the rehabilitation of stroke patients. Articles that brought this theme were analyzed. The general objective was to evaluate the efficacy of early mobilization to improve the functional capacity of post-stroke patients. A randomized observational study was carried out to analyze eleven articles and the efficacy of the PM in functional rehabilitation. Methodologically the studies were evaluated using the PEDro platform quality scale, which were weighted and used for the base results. The initial results of the studies were made by a flowchart that consisted of 1,074 articles, which after an initial examination of title and abstract and subsequent full examination ended up in 11 articles. It can be seen in the discursive and conclusive analysis that the use of PM can be an effective factor in the functional recovery of patients in the post-stroke stage.